STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PEMENFAATAN FASILITAS SEKOLAH DI SDN 04 TENGGULI TAHUN PELAJARAN 2023-2024 - Lilis Duwanti; Ubabuddin, Sera Yuliantini (ADISAM PUBLISHER, 2025)
The purpose of this study is to reveal, 1) to describe the learning motivation of students through the utilization of school facilities at SDN 04 Tengguli in the 2023-2024 Academic Year, 2) to find out what factors influence the lack of learning motivation of students at SDN 04 Tengguli in the 2023-2024 Academic Year, 3) to find out the teacher's strategy in utilizing school facilities to increase the learning motivation of students at SDN 04 in the 2023-2024 Academic Year. This study uses a descriptive research type with a qualitative approach. Data collection techniques using interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation (data display), and drawing conclusions. The results of this study indicate that; 1) Student learning motivation through the use of school facilities at SDN 04 Tengguli is one of the keys to learning success and self-development, learning motivation is an important role in influencing the learning process to achieve educational goals, both from within students and from outside students so as to create enthusiasm in learning in order to achieve a goal, such as being active in participating in learning, doing assignments, and doing homework, being active in learning, actively doing assignments, and utilizing library facilities by reading books. 2) Factors that influence the lack of student learning motivation at SDN 04 Tengguli are a sense of inability to understand or inability to master ordinary lesson materials, students will tend to experience a decrease in learning motivation, student health can interfere with the comfort and concentration of students in learning, resulting in a decrease in learning motivation, the factor of the absence of ideals or goals in students can affect the lack of learning motivation. 3) Teachers' strategies for utilizing school facilities to increase students' learning motivation at SDN 04 Tengguli. Utilizing facility-based learning planning at school, such as implementing facility-based learning planning, is a very important step